2023
DOI: 10.1002/suco.202201227
|View full text |Cite
|
Sign up to set email alerts
|

3D‐printed concrete footbridges: An approach to assess the sustainability performance

Javier Asensio,
Irene Josa,
Andrea Monserrat
et al.

Abstract: Digital fabrication with concrete (DFC) is fast becoming an attractive alternative for components (i.e., façades, urban furniture) and structural typologies (i.e., short‐span footbridges, columns, floor systems) for which complex geometries derived from particular aesthetical criteria and/or construction time constrictions are governing parameters. Additionally, some authors claim that this process allows improving the sustainability of structures, as less material is necessary compared to traditional concrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Regarding sustainability, Asensio et al [46] quantified the environmental impact of 3D printing technology and identified that, while 3D printing generates fewer greenhouse gas emissions than conventional solutions, there is still room for improvement in economic indicators for competitive solutions. Placzek et al [47] integrated 3D printing with lean manufacturing techniques, prioritizing on-demand production and bi-directional digital workflows to reduce material waste.…”
Section: Production Phase 421 Digital Manufacturingmentioning
confidence: 99%
“…Regarding sustainability, Asensio et al [46] quantified the environmental impact of 3D printing technology and identified that, while 3D printing generates fewer greenhouse gas emissions than conventional solutions, there is still room for improvement in economic indicators for competitive solutions. Placzek et al [47] integrated 3D printing with lean manufacturing techniques, prioritizing on-demand production and bi-directional digital workflows to reduce material waste.…”
Section: Production Phase 421 Digital Manufacturingmentioning
confidence: 99%
“…These analyses include evaluations focused on different types of structures and materials. For example, in structural analyses, it has been applied to tunnels [5][6][7][8][9], bridges [10,11], and footbridges [12,13], industrial buildings [14][15][16] or skyscrapers [17], mass housing [18], and modular residential towers [19]. It has also been used in assessing temporary [20][21][22][23], and self-promoting housing [24], as well as in evaluating the sustainability of construction materials like wood [25,26], concrete [27], and prefabricated structures [28].…”
Section: Introductionmentioning
confidence: 99%